Digital Content Marketing sebagai Media Pemasaran Lembaga Pendidikan di Universitas Al-Amien Prenduan - Wardi, Moh.; Bidaula, Zian Salsabila (Intelektual: Jurnal Pendidikan dan Studi Keislaman, 2025)
Digital content marketing (DCM) has proven to be an effective strategy for expanding brand reach and increasing sales, including educational institutions requiring publications for their sustainability. This study aims to analyze the implementation of DCM at Universitas Al-Amien Prenduan as a promotional medium to improve marketing and the quality of the educational institution. This study uses a case study approach with data collection through interviews, observations, and documentation involving students, lecturers, and staff. The results show that UNIA has implemented DCM since 2017, focusing on institutional strengthening, human resource (HR) development, and creative content publication. The positive impacts of this implementation include increased credibility, reach, and student numbers, although the increase is not immediately visible. The challenges faced include limited HR and a lack of adaptation to new media. The conclusion of this study shows that overall, the implementation of digital content marketing has a positive impact on improving the quality of the educational institution.